Aesthetic Form and the Political: Two Perspectives on Protest in the Choreography of William Forsythe and Kevin Iega Jeff. Issue 2 (3rd May 2020) - Fernando, Tanya Jayani
Abstract: This essay examines two concert dance pieces on the Gulf Wars: Kevin Iega Jeff's Church of Nations (1991) and William Forsythe's Three Atmospheric Studies (2006). While both are works of protest, they draw from different aesthetic traditions: the Black aesthetic and postmodern aesthetic, respectively. In an effort to think through the relationship between aesthetic form and the political, the essay explores what is at stake in such a comparison. "Aesthetic Form and the Political" is the complementary essay to "The Ekphrastic Body: Wayne McGregor's Woolf Works, " Dance Chronicle 42, no. 2 (2019): 143–69, https://doi.org/10.1080/01472526.2019.1625651 .